2017
DOI: 10.1186/s40497-017-0066-2
|View full text |Cite
|
Sign up to set email alerts
|

Implication of attitude of graduate students in Oman towards entrepreneurship: an empirical study

Abstract: The purpose of the paper is to assess the implication of attitude of graduate students in Oman towards entrepreneurship. Exploratory factor analysis (EFA), and a multivariate regression model were used to assess the attitude and identify its influencing factors. Data was collected through a structured questionnaire, with a sample of 165 students, selected from four colleges in Muscat. Results show that although graduates in Oman have a positive attitude towards entrepreneurship, preference to start their own b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
31
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 27 publications
5
31
0
1
Order By: Relevance
“…This points to the fact that a lot of concerted efforts by various stakeholders are still required. Change of approach by leadership may also be necessary because it will determine attitudes towards entrepreneurship (Omer, et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…This points to the fact that a lot of concerted efforts by various stakeholders are still required. Change of approach by leadership may also be necessary because it will determine attitudes towards entrepreneurship (Omer, et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…But many of the early findings from this first research stream had low explanatory power or poor replicability, especially when other potential sources of variance were adequately controlled, and have not been found to generalize across very different cultures or levels of economic development (Pinillos & Reyes, 2011;Siu & Lo, 2013). Moreover, the effects of individualism/collectivism and of uncertainty avoidance in a national culture seem to operate differently on specific aspects of the entrepreneurial function (Ibrahim, Devesh, & Ubaibullah, 2017). For example, Autio et al (2013) found that a collectivist culture has a negative influence on entrepreneurial entry, but a positive influence on entrepreneurial growth aspirations.…”
Section: Literature Of Culture and Entrepreneurshipmentioning
confidence: 97%
“…According to Davari and Farokhmanesh (2017), financial support is an important barrier to entrepreneurship. Wealthier people enter entrepreneurship in greater numbers compared to individuals who lack financial support (Ibrahim et al, 2017). Engelschiøn (2014) has shown that young individuals tend to pursue entrepreneurship because they are more likely to take occupational risks for high profits.…”
Section: Financial Support and Entrepreneurial Attitudementioning
confidence: 99%